Entrepreneurial ventures and wage differentials between Germans and immigrants - Amelie Constant; Yochanan Shachmurove (Institute for the Study of Labor (IZA), 2003)
This paper focuses on the entrepreneurial undertaking of immigrants and natives in Germany. We first study factors that affect the sorting of individuals into self-employment and then we investigate whether self-employment has a differential effect on the wages of individual workers and can lead them to economic success. We employ recent data from the German Socioeconomic Panel that allow us to identify and compare four distinct groups: West Germans, East Germans, guestworkers, and ethnic Germans. We find that the probability of self-employment increases significantly with age for all groups. For immigrants, the years-since-migration exhibits a U-shape. During the first years since migration the likelihood of self-employment decreases over time. However, when immigrants have accumulated more years of residence in Germany, the likelihood is increasing again. This suggests that once immigrants have overcome the initial adjustment shock, self-employment is a means to take advantage of the opportunities of the host country and achieve a higher socio-economic standing. Among immigrants, guestworkers are twice as likely to choose selfemployment as ethnic Germans. Further, we find that self-employment is a lucrative choice only for Germans who are in the upper end of the income distribution. 'Rich' self-employed Germans enjoy a wage premium compared to their salaried counterparts. However, immigrants are able to traverse the socioeconomic gap through self-employment, irrespective of the part of the distribution they are at. Self-employed immigrants earn 22% more than the salaried immigrants.
Keywords: J23; M13; J24; J61; J31; 330; entrepreneurship; self-employment; occupational choice; immigrants; wage; differentials; Entrepreneurship-Ansatz; Selbstständige; Ausländer; Lohnstruktur; Einkommen; Ausländische Arbeitskräfte; Deutsche; Schätzung; Deutschland